Entre a graça, o axé e o dharma: uma análise comparativa das políticas públicas responsáveis pelo processo de reconhecimento do patrimônio de religiões acatólicas - Sales, Alberlene Baracho (2021)
Brazil is a multi-religious country, with a noteworthy ethnic and cultural variety. Nevertheless, during many years of our history, only one religion was contemplated by heritage public policies as though only the Catholic religion represented the whole country. Our research proposes to analyze the process of recognition of non-catholic religions, how they influenced and conquered space for recognition among the embargoes that occurred as a consequence of religious and/or ethnic intolerance. The heritage public policies comprise the recognition, conservation and protection of tangible and intangible cultural assets that are considered the common property of the population. In this research, we specifically selected the built heritage of three different religions that have marked the history of our country, namely: the Presbyterian Cathedral in Rio de Janeiro-RJ-Brazil; the Terreiro de Candomblé Ilê Axé Oxumaré in Salvador, Bahia-Brazil; and the Shin Buddhist Temple Terra Pura, Brasília-Brazil. In bibliographic research, of ethnographic scope, we trace a determinant that presents the existing interconnection between identity-architecture-religion, which directs us to understand the steps between intolerance and recognition.